Evaluating the effect of structural and parametric change of weft knitted polyester fabrics over the performance of sportswear - Muhammad Owais Raza Siddiqui; Salma Farooq; Muhammad Dawood Husain; Hassan Ali; Saira Faisal (Mehran University Research Journal of Engineering and Technology)
Using the 100% polyethylene Terephthalate (PET) 75/72 DTY semi-intermingle yarn, three different weft-knitted structures are manufactured on similar gauge circular weft knitting machines. All the manufactured structures are tested using standard methods so that the influence of knitting parameters and optimization of structures on the overall performance of sportswear can be analysed. The structural characteristics including, stitch length, stitch density, thickness, GSM, dimensional stability, spirality, pilling, abrasion, and bursting strength are measured. Similarly, OMMC, air permeability, and stretch and growth properties were evaluated to assess the functional performance and relative hand value of the developed knitted fabric. It was found that the structural and knitting parameters have an adequate influence over the functional properties of sportswear which should be designed and optimized as per the need and intensity of sports.